ASPEK KEPERILAKUAN PADA SISTEM INFORMASI AKUNTANSI DALAM PENGAMBILAN KEPUTUSAN ORGANISASI - Duwi Riningsih (POLITEKNIK CAHAYA SURYA, 2018)
The accounting informatic system in any economic organisation has the role to show the information and outcomes of company economic performance in a format that is beneficial and useful to accountants and managers in order to ensure the good running of their companies. Thus, when information is necessary to substantiate a decision in terms of economic matters, the field of financial accounting data along with the related informatic system provide the information needed.Managers who receive responsibility have an obligation to maximize the welfare of the owners Short and long period of time. On the other hand, managers also have the same interests with the owner, is to maximize the welfare of their self review. The presence of two agents to the impact of interest problem. This condition can make manager to do a disfuctional behaviour, so the impact of disfuctional behaviour is incorrect information and can be influence to decision making. Keywords : Accounting Information System, Agency Theory, Behaviour Accounting, Decision Making.